Memes and Interactivity of Facebook Mobile Legends Gamers After the Fall of RRQ - Dwi Prasetyo Yulianto; Moch Fuad Nasvian; Dimas Rifqi Novica (LONTAR: Jurnal Ilmu Komunikasi, 2024)
This research aims to determine the level of interactivity in meme postings by netizens during the M4 World Tournament of the game Mobile Legends: Bang Bang (MLBB). Utilizing the Facebook platform, specifically the "Mobile Legends Gamers'' group, this study analyzed 791 comments from 10 group member posts during the period of January 10 - 25, 2022. Employing Thematic Analysis, interactivity dimensions were examined based on the framework of Six Basic Emotions and Message Interactivity. Results indicate that interactivity among group members was high, with various emotions revealed, such as happiness over RRQ's defeat and anger at mistakes made by favorite teams. In conclusion, social media plays a significant role in fostering user interactivity and emotions, especially within the context of gaming communities like MLBB. This study offers valuable insights for the Mobile Legends community and the field of digital communication science, emphasizing how memes are used as a means of communication on social media.